Relationship of Sleep Quality and Academic Burden with Premenstrual Syndrome in University-Level Female Athletes - Sana Akbar; Madiha Batool; Fouzia Parveen; Amina Tahir; Khawaja Muhammad Moosa Naik; Asim Akbar*, (Dialogue Social Science Review (DSSR), 2025)
Premenstrual syndrome (PMS) is a prevalent health concern among female athletes, potentially impacting both academic performance and sports participation. Sleep quality and academic burden are two lifestyle factors that may influence PMS severity, yet their combined effect in university-level female athletes remains underexplored. This study aimed to examine the relationship between sleep quality, academic burden, and PMS severity among university-level female athletes, and to determine the predictive power of these factors on PMS symptoms. A cross-sectional study was conducted with a sample of 120 female athletes enrolled in various sports programs at the university level. Participants completed the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, the Academic Stress Scale (ASS) to measure academic burden, and the Premenstrual Symptoms Screening Tool (PSST) to evaluate PMS severity. Descriptive statistics, Pearson correlation, and multiple regression analyses were performed. Findings revealed that 68.3% of participants reported poor sleep quality, and 59.2% experienced moderate-to-high academic burden. Both poor sleep quality (r = 0.62, p < .001) and academic burden (r = 0.47, p < .001) were significantly correlated with PMS severity. Regression analysis indicated that sleep quality (β = 0.51, p < .001) was the strongest predictor of PMS severity, followed by academic burden (β = 0.34, p < .01), explaining 48% of the variance. Poor sleep quality and academic burden significantly contribute to PMS severity in university-level female athletes. Interventions targeting sleep hygiene improvement and academic stress management may help reduce PMS-related discomfort and optimize both athletic and academic performance. Keywords: Sleep Quality, Academic Burden, Premenstrual Syndrome, Female Athletes, University Students, Sports Performance